How Do Residents Spend Their Time in the Intensive Care Unit?. (November 2015) - Carayon, Pascale; Weinger, Matthew B.; Brown, Roger; Cartmill, Randi S.; Slagle, Jason; Van Roy, Kara S.; Walker, James M.; Wood, Kenneth E.
Abstract: Purpose: To describe the work of residents and the distribution of their time in 6 intensive care units (ICUs) of 2 medical centers (MCs). Methods: A total of 242 hours of observation to capture data on tasks performed by residents in 6 ICUs, including adult, pediatric, medical and surgical units, were conducted. For each observation period, the percentages of total time spent on each task and on the aggregated task categories were calculated. Results: Overall, while in the ICUs, residents spent almost half of their time in clinical review and documentation (19%), conversation with team physicians (16%), conversation attendance (6%) and order management (6%). The 2 MCs differed in the time that residents spent on administrative review and documentation (4% in one MC and 15% in the other). The pediatric ICUs were similar in the 2 MCs, whereas the adult ICUs exhibited differences in the time spent on order management and administrative review and documentation. Conclusions: While in the ICUs, residents spent most time performing direct patient care and care coordination activities. The distribution of activities varied across 2 MCs and across ICUs, which highlights the need to consider the local context on residents' work in ICUs.